A homiletika oktatás kezdetei a pesti teológián, Székács József kéziratainak tükrében - SZETEY, Szabolcs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
The Beginning of Homiletics Education at the Theology in Pest, in the Light of the Manuscripts of József Székács The Faculty of Theology in Pest opened its doors in 1855. The institution cooperated with the Lutheran Church in the first ten years. During this time, future Lutheran Bishop József Székács led the studies of homiletics. This data can be found in the Ráday Archives with the list of professors and popular study books they used. We also discovered the fact from the timetables that Székács taught homiletics practice to four different grades at the same time, usually at his parish. We can find Székács’s heritage in the National Lutheran Archives, such as his letters, notes, sermons, and so on. I carried out research on his homiletics manuscripts, from which I would like to highlight his memo titled A gyakorlati homiletika alapja 1858/9 [The Journal of Practical Homiletics 1858/9]. The memo includes recommendations for his students about preaching preparations for Christmas, Good Friday, and Easter. Székács’s work is particularly pragmatic, and therefore it successfully guides the pastor students through the steps of preparing a good sermon.